2021
DOI: 10.1073/pnas.2021818118
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytotoxic Eomes-expressing CD4 + T cells in secondary progressive multiple sclerosis

Abstract: Multiple sclerosis (MS), a putative autoimmune disease of the central nervous system (CNS), commonly presents as relapsing-remitting MS (RRMS), characterized by recurrent episodes of peripheral disabling symptoms resulting from inflammatory CNS damage. Many RRMS patients transition to a chronic disease course with progressive neurological dysfunctions (secondary progressive MS, SPMS), with the progression rate varying between patients and over time. SPMS pathogenesis is now linked to immune-cell–mediated proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 56 publications
(56 reference statements)
3
47
0
Order By: Relevance
“…Interestingly, we found that CD4 cells in the spinal cord were cytotoxic by highly expressing Granzyme(s) and cognate serine protease inhibitor Serpin(s) along with IFNg and GM-CSF (Figure 1F). Indeed, this finding matches with the human MS study that CD4 cells from human secondary progressive MS autopsy brain samples are cytotoxic by co-expression of Eomes and Granzyme-B (19).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, we found that CD4 cells in the spinal cord were cytotoxic by highly expressing Granzyme(s) and cognate serine protease inhibitor Serpin(s) along with IFNg and GM-CSF (Figure 1F). Indeed, this finding matches with the human MS study that CD4 cells from human secondary progressive MS autopsy brain samples are cytotoxic by co-expression of Eomes and Granzyme-B (19).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, we observed that the expression (raw counts) of CD28 mRNA was generally low, especially in cells with high expression of GZMB in Th17-polarized cells in coculture with OLs by single-cell RNA sequencing ( Supplementary Figure 9B ). Granzyme B levels are elevated in the CSF of MS patients ( 42 ) and CD4 + T cells from MS patients secrete more granzyme B than healthy controls in the relapsing–remitting ( 85 ) and progressive forms ( 86 ). In addition, pro-inflammatory CD4 + T cells secreting granzyme B can disrupt the blood–brain barrier ( 87 ) and cause glial fibrillary acid protein fragmentation in human primary astrocytes in vitro ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…73 Moreover, the abundance of GZMB-expressing Eomes + T helper cells increased in the pathogenesis of secondary progressive multiple sclerosis. 74 These studies demonstrate the potential utility of GZMB and GZMB + cells as a marker for the identification, diagnosis and treatment of a variety of diseases.…”
Section: Gzmb and Elimination Of Viruses Or Virus-infected Cellsmentioning
confidence: 78%